Good governance according to Islamic perspective - Mohamad Yunus, Mohamad Ismail (jurnal.fh.unila.ac.id, 2017)
The objectives of the professional agencies must embody provisions that promote good governance and embrace values of integrity and accountability and seek support from the public and the government of the day to provide an independent view on all matters. The universal truth is that everything should be done in the public good. Professionals form the backbone of human infrastructure in any economy, politics, social and legal growth. Their contributions through professional performance enhance the good delivery system that facilitates policies making and management for public sector. They provide the skills and talent in balancing the pursuits of maximization of services. The expression “good governance” has been constantly used lately in both public sector as well as private sector in Malaysia. In the context of a private body, it should be within the framework of the statute, which governs the body and also its constitution. In the public sector, it means that the administrators should act professionally and not to abuse or misuse the power or authority given to them. They are regarded as the trustees of the public at large. The scope of this article is on good public governance in the public sector or to be exact, good governmental administration as interpreted by the judiciary especially through its judicial review power and Islamic Perspective based on the principles of Maqasid As Shariah (Objectives of Islamic Law).